NGOs' Role in Sustaining Indigenous Knowledge in RuralBangladesh: Agriculture, Healthcare, and Disaster Management - Ullah, M D Rahmat (South Asian Journal of Social Sciences and Humanities, 2024)
This paper explores the indispensable role of non-governmental organizations (NGOs) in cultivating, applying, and conserving Indigenous knowledge within rural Bangladesh. It scrutinizes how NGOs sustain Indigenous knowledge by focusing on pivotal sectors like agriculture, local medicine, and disaster management. Employing qualitative methodologies—such as ethnographic interviews, focus group discussions (FGD), and case studies—the research was conducted in the Gabura union, Bangladesh, using primary and secondary data sources. The literature review underscores the significance of Indigenous knowledge in agriculture and disaster management while identifying gaps in comprehending knowledge conservation dynamics and the NGO's impact on Indigenous knowledge. It highlights how locals employ Indigenous Knowledge to combat natural disasters, particularly in agriculture, healthcare, and disaster management. Furthermore, it explores NGOs' active roles in preserving and leveraging Indigenous Knowledge, emphasizing its integration with modern scientific knowledge and significance in rural life. The study delves into Gabura residents' strategies for cyclone resilience, such as seeking refuge on embankments, relocating to higher ground, and preserving seeds and dry food. It emphasizes NGOs like BARCIK and their initiatives—Paramela and Kaviraj Mela—along with resource person engagement and safeguarding local knowledge endangered by globalization. BARCIK's training in disaster management, advocacy for traditional agricultural methods, and promotion of indigenous remedies in healthcare are highlighted. Ultimately, the paper underscores NGOs' significant contributions to fostering and applying Indigenous knowledge for sustainable rural development. It emphasizes the institutional processes in defining knowledge and the NGO's role in its reproduction.
Keywords: Indigenous Knowledge; Non-Governmental Organizations (NGOs); Rural Bangladesh; Agriculture; Healthcare; Disaster Management